CARANDIRU: ENSAYO SOBRE CRÍTICA, REGLAS Y ORDEN SOCIAL - Gadea, Carlos A. (Universidad de Costa Rica, 2023)
This article brings up the discussion about diciplinament, the control society and the supposed connotation of some sort of social critics towards the “order” legitimized by the modern dynamic. Briefly analysing the instigating film Carandiru (EE.UU - Brazil, 2003), by the director Héctor Babenco, presents an intention to delineate some characteristics that nowadays take on social rules and the change of perspective in the sociability in which it acts, apparently, from the transition of a diciplinament society to a control society. An interesting turn that warns the social-cutural game which throws our sociabilities into scepticism, contingency, multiplicity of the social scenes and to the possible spaces and faith of the critics on eventually post-modern situations.